Accountability and Transparency in the Public and Private Sector - Muhammad Adil; Mediaty; Haliah (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
This paper aims to look at research development trends and future directions regarding accountability and transparency. This paper is important because it can be a reference for researchers who want to research on accountability and transparency. This paper uses a critical review analysis method. The results show that research on accountability and transparency at this time is still filled with public services, village fund financial management, mosque financial management. According to the author, this kind of theme will continue to exist and develop according to the times. Research on the accountability of aid funds is interesting to study.